A Meta-Analysis of Transcranial Direct Current Stimulation on Substance and Food Craving: What Effect Do Modulators Have? - Chen, Jiasi; Qin, Jingmin; He, Qinghua; Zou, Zhiling (Frontiers in Psychiatry, 2020)
Substance addiction and food addiction are big social problems all over the world. Previous studies on substance addiction have used transcranial direct current stimulation (tDCS) to influence craving of substance or food. However, the reported effects are not always consistent due to inconsistent experimental settings. The way how modulators affect the effect of tDCS on substance addiction is worth exploring. This meta-analysis was conducted to evaluate the effect size of tDCS on substance and food craving and investigate the influence of potential modulators. We systemically identiﬁed and reviewed studies on substance/food craving using tDCS that were published between January 2008 to January 2020. A total of 32 eligible studies were identified. Hedge’s g was computed as an indicator of the effect of tDCS and some potential moderators (substance type, stimulation sites, current intensities, number of sessions, duration of single stimulation, and study design) were examined using subgroup analysis. Random effects analysis revealed a total medium effect size (Hedge’s g = 0.536, 95%CI: 0.389–0.683, after adjusting Hedge’s g =0.416, 95%CI: 0.262–0.570), favoring active over sham stimulation in the reduction of craving. There was a significant difference between the number of sessions (repeatedly stimulation was better than once). No other significant differences were found in other subgroups analysis. In conclusion, our results provided evidence that tDCS can be an effective way to reduce craving of substance or food, multi-stimulation can more effectively reduce cravings but the influences of modulators still need be to be examined in depth in future.